Psalm 100 - uitbundige lof oor die Godheid, goedheid en grootheid van Jahwe - Mar, L. P. (Old Testament Essays, 2000)
Psalm 100 contains poetry of the highest quality. Although it is a very short psalm, it carries a great message. Yahweh is glorified because he is God, because he is good, and because he is great. The psalmist makes ues of several poetical features in his structuring of the psalm to convey this message. The praise offered to God in this psalm is not the 'easy' praise of prosperity theology, but it is offered by people who are familiar with pain and suffering. The divine nature, goodness, and greatness of Yahweh is experienced through the trials of this life.
free
Keywords: Christianity; Psalm 100